The Representation of Love in Nizar Qabbani's Poem "Uhibbuki Uhibbuki wal Baqiyatu Ta'ti": A Balāghah-Based Study of Kinayah - Al Jafarie, Hafidz Abdullah Azzam; Zuhdy, Halimi (Mantiqu Tayr: Journal of Arabic Language, 2026)
This study examines the use of indirect expressions in Nizar Qabbani’s poem “Uḥibbuki Uḥibbuki wal-Bāqiyātu Taʾtī” to uncover the multidimensional meanings of love conveyed through symbolic and figurative language. As a leading figure in modern Arabic poetry, Qabbani employs indirect expressions to represent emotional depth, psychological nuance, and humanistic values within the experience of love. This study aims to identify the types of indirect expressions used in the poem namely talwih, ta‘ridh, ramz, and ima’/isyarah and to analyze how these expressions articulate the dimensions of love proposed by Erich Fromm, including care, responsibility, respect, and knowledge. The scope of this study is limited to a stylistic and textual analysis of a single poem using the framework of balaghah and humanistic psychology.This research uses a qualitative content analysis method. The primary data consist of Qabbani’s poetic text, while the secondary data are drawn from scholarly works on balaghah, modern Arabic poetry, and Erich Fromm’s theory of love. Data collection was conducted through close reading and systematic note-taking, followed by data reduction, data presentation, and conclusion drawing. The findings reveal that Qabbani’s indirect expressions form layered meanings of love that reflect Fromm’s concept of productive love. These expressions enhance the poem’s aesthetic quality while simultaneously deepening its psychological and humanistic resonance. This study contributes to the field of modern Arabic literary studies by integrating rhetorical analysis with psychological theory. Future research is encouraged to examine a broader corpus of Qabbani’s poetry, apply comparative approaches, or employ interdisciplinary perspectives to further explore representations of love in modern Arabic literature.